2020
DOI: 10.1016/j.isci.2020.101664
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Stress Pathway that Parallels Cytoplasmic Stress Granule Formation

Abstract: Summary Stress adaptation is exploited by cancer cells to survive and proliferate under adverse conditions. Survival pathways induced by stress are thus highly promising therapeutic targets. One key pathway involves formation of cytoplasmic stress granules, which regulate the location, stability, and translation of specific mRNAs. Here, we describe a transcriptional stress response that is triggered by similar stressors and characterized by accumulation of RepoMan (cell division cycle associated 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The percentage of various studies is shown in Figure 2. Meanwhile, the majority of studies, about 66% of studies, are dedicated to cell culture studies only (Baguet et al, 2007;Miyoshi et al, 2007;Arimoto et al, 2008;Eisinger-Mathason et al, 2008;Goulet et al, 2008;Busà et al, 2010;Gottschald et al, 2010;Guo et al, 2010;Kalra et al, 2010;Nikpour et al, 2011;Taniuchi et al, 2011aTaniuchi et al, ,b, 2014Park et al, 2012;Fournier et al, 2013;Pizzo et al, 2013;Thedieck et al, 2013;Chang et al, 2014;Kano et al, 2014;Podszywalow-Bartnicka et al, 2014;Yuan et al, 2014;Liu et al, 2015;Somasekharan et al, 2015;Szafron et al, 2015;Valentin-Vega et al, 2016;Weeks et al, 2016;Narayanan et al, 2017;Wall and Lewis, 2017;Takayama et al, 2018;Haghandish et al, 2019;Heberle et al, 2019;Kashiwagi et al, 2019;Mazloomian et al, 2019;Cui et al, 2020;Do et al, 2020;Brown et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of various studies is shown in Figure 2. Meanwhile, the majority of studies, about 66% of studies, are dedicated to cell culture studies only (Baguet et al, 2007;Miyoshi et al, 2007;Arimoto et al, 2008;Eisinger-Mathason et al, 2008;Goulet et al, 2008;Busà et al, 2010;Gottschald et al, 2010;Guo et al, 2010;Kalra et al, 2010;Nikpour et al, 2011;Taniuchi et al, 2011aTaniuchi et al, ,b, 2014Park et al, 2012;Fournier et al, 2013;Pizzo et al, 2013;Thedieck et al, 2013;Chang et al, 2014;Kano et al, 2014;Podszywalow-Bartnicka et al, 2014;Yuan et al, 2014;Liu et al, 2015;Somasekharan et al, 2015;Szafron et al, 2015;Valentin-Vega et al, 2016;Weeks et al, 2016;Narayanan et al, 2017;Wall and Lewis, 2017;Takayama et al, 2018;Haghandish et al, 2019;Heberle et al, 2019;Kashiwagi et al, 2019;Mazloomian et al, 2019;Cui et al, 2020;Do et al, 2020;Brown et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The stages of metastasis can be summarized in the steps of local invasion, intravasation by blood/lymphatic circulation, and extravasation in new tissue and proliferation and angiogenesis, respectively (Figure 4; Shelton et al, 2010). Meanwhile, the stresses that enter the cancer cells push the situation in a direction to dysregulate the equilibrium of SGs and use SGs as an advantage in cancer conditions to benefit cancer cells (Anderson et al, 2015;Do et al, 2020).…”
Section: Cancer Formation Progression and Metastasismentioning
confidence: 99%
“…Alternatively, this also suggests in situ proteotoxic stress to recruit the effectors into the nucleus. Inhibition of eIF2α phosphorylation by trans-ISRIB and protein synthesis by CHX has been shown to reverse the accumulation of stress granules induced by arsenite but fails in nuclear stress foci formation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%